Objektifikasi Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan (Sebuah Gagasan Pemikiran) - Dikson T. Yasin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
This study analyzes the modern legal formulation in the formulation of Islamic marriage law in Indonesia. Therefore, the objective considerations in establishing the rule of law a marriage becomes absolutely necessary. In addition, the formulation must produce the material marriage laws within the context of socio-cultural and socio-historical Indonesian Islamic community. With the approach of social history, this study would like to assert that the products Islamic marriage law Indonesia should not only by tradition inherited from generation-a generation ago, but required a study approach to social history with attention and consider the social life of the Indonesian Islamic community who step toward community modern Islam. It is characterized by the marriage laws that are applied to the Indonesian Islamic community in the form of legislation, namely Law No. 1 of 1974. When the Indonesian Islamic marriage law has been codified into national law, then the legislation can be regarded as consensus of Indonesia, or can be viewed as an Indonesian fiqh formulations.